A catalogue of the holotypes of chigger mites (Acariformes: Trombiculidae) at the Natural History Museum of Geneva - Stekolnikov, Alexandr A. (Zootaxa, 2019)
The personal collection of P.H. Vercammen-Grandjean, which is deposited in the Natural History Museum of Geneva (Switzerland), is revised and a catalogue of holotypes is compiled. The inventory includes data on the holotypes of 92 valid trombiculid species, 18 specimens erroneously labeled as holotypes and 84 specimens designated as holotypes of unpublilshed species (nomina nuda).